Tributação e desenvolvimento econômico regional: um exame da tributação como instrumento de regulação econômica na busca da redução das desigualdades regionais - Elali, André de Souza Dantas (2006)
On this legal research the objective is to demonstrate as object of the study the taxation as an instrument of regulation in the search of the reduction of the regional inequalities. It recognizes as an objective of the Brazilian State the economical development. Through the hypothetical-deductive, bibliographical and argumentative methods the research bases on the relation between the economical law and the tax law. It considers important some techniques and information imported from economics and economical analysis of law - the Law and Economics. In the first chapter the study examines the State in face of the purposes of the Constitution and of the federalism. Analyses also the relation between legal system rules, market and competition. It establishes the power of economics as a structural base of the social system and emphasizes the socioeconomic function of the economical activities. After that, the research dedicates to taxation and it s regulatory function. It is demonstrated how may State regulate private activities in order to reach development and to reach the regional and social inequalities. It also studies the importance of tax expenditures. The last part is dedicated to the conclusive synthesis of the research.